2012
DOI: 10.3989/arbor.2012.756n4008
|View full text |Cite
|
Sign up to set email alerts
|

El impacto de Internet en la participación política: Revisando el papel del interés político

Abstract: In this paper we aim to investigate the relationship between Internet use, motivation and political participation. In particular, we aim to find out if, by reducing participation costs, use of the Internet changes the importance of motivation in the classic explanations of participation. In order to explore this question, we have used data from survey 2736 by the Centro de Investigaciones Sociológicas (CIS), which addresses the issue of political participation andInternet use. The analysis shows that Internet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
19

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
(26 reference statements)
0
3
0
19
Order By: Relevance
“…However, authors such as Borge et al (2012), argue that online forms of engagement complement, but do not replace, those forms built in the physical environment, and do not mobilise new individuals but only reinforce the engagement of those who are already involved. For a decade, several authors have questioned that citizen participation goes in a double direction (Sampedro et al, 2008;Dader et al, 2011;Calvo et al, 2014;Dader et al, 2017, Dader et al 2014.…”
Section: Uses Of Social Network Consequences On Participationmentioning
confidence: 99%
“…However, authors such as Borge et al (2012), argue that online forms of engagement complement, but do not replace, those forms built in the physical environment, and do not mobilise new individuals but only reinforce the engagement of those who are already involved. For a decade, several authors have questioned that citizen participation goes in a double direction (Sampedro et al, 2008;Dader et al, 2011;Calvo et al, 2014;Dader et al, 2017, Dader et al 2014.…”
Section: Uses Of Social Network Consequences On Participationmentioning
confidence: 99%
“…This direct relationship between offline and online participation is also raised by Borge et al (2012) based on the theory of normalization by Margolis and Resnick (2000), who observed that individuals perform the same participatory actions in the digital environment that they have already developed offline; social media, and in general the Internet, do not increase the number of participants, but reinforce the participation of those already involved.…”
Section: Social Movements and Participation In The Digital Spherementioning
confidence: 90%
“…No obstante, autores como Borge et al (2012) sostienen que las formas online de compromiso complementan, pero no sustituyen, a las construidas en el entorno físico, no movilizan a nuevos individuos, sino que solo refuerzan los compromisos de los ya implicados. Desde hace una década diversos autores han puesto en tela de juicio que la participación ciudadana vaya en una doble dirección (Sampedro et al, 2008;Dader et al, 2011;Calvo et al, 2014;Dader et al, 2017, Dader et al 2014.…”
Section: Marco Teórico 21 Usos De Las Redes Sociales Consecuenciasunclassified